1988
DOI: 10.1161/01.cir.77.4.873
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronary angioplasty on coronary flow reserve.

Abstract: To determine the effects of coronary angioplasty on coronary flow reserve (CFR), we studied 32 patients before and immediately after single-vessel coronary angioplasty and 31 patients evaluated late after angioplasty (7.5 + 1.2 months, mean + SEM). The geometry (percent area stenosis and minimal cross-sectional area) of each lesion was determined by quantitative coronary angiography (Brown/Dodge method) and the integrated optical density was measured by videodensitometry. CFR was measured with a No. 3F coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
3
3

Year Published

1989
1989
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(162 citation statements)
references
References 47 publications
8
148
3
3
Order By: Relevance
“…In agreement with several studies, [5][6][7] we found an elevation of baseline APV as a contributing factor for a low postproce- *Variables include age, sex; and a history of diabetes, hypertension, smoking, previous MI, or revascularization. Functional angina class; baseline heart rate, systolic blood pressure, and diameter stenosis; and lesion characteristics (angulation, calcification, bifurcation, and contour) were not independent predictors.…”
Section: Determinants Of Impaired Cfvr After Angioplastysupporting
confidence: 91%
“…In agreement with several studies, [5][6][7] we found an elevation of baseline APV as a contributing factor for a low postproce- *Variables include age, sex; and a history of diabetes, hypertension, smoking, previous MI, or revascularization. Functional angina class; baseline heart rate, systolic blood pressure, and diameter stenosis; and lesion characteristics (angulation, calcification, bifurcation, and contour) were not independent predictors.…”
Section: Determinants Of Impaired Cfvr After Angioplastysupporting
confidence: 91%
“…There are indications, however, that the myocardial microvasculature can be affected by the invasive procedure itself. 19 Therefore, another confounding factor was introduced, making the conclusions from these studies debatable. In our protocol, such confounding is prevented by performing all measurements after stent placement.…”
Section: Protocol For Inducing Variable Stenosismentioning
confidence: 99%
“…[1][2][3] The restenotic lesion may impair coronary blood flow, reduce coronary arterial flow reserve (CAFR), limit exercise tolerance, and precipitate chest pain. 4,5 Most individuals who have chest pain in the months after a successful percutaneous intervention require contrast coronary angiography for the definitive identification of restenosis. 6,7 A noninvasive method for reliably identifying restenosis would have substantial clinical utility.…”
mentioning
confidence: 99%